INTEGRATED VOTER EDUCATION MODEL TO STUDENTS AS PRE-VOTERS - Hariyanti, Hariyanti; Darmawan, Cecep; Rahmat, Rahmat; Anggraeni, Leni; Radini, Radini; Abdullah Hasibuan, Hamdi (JWP (Jurnal Wacana Politik), 2026)
This research aims to describe the importance of preparing pre-voters to become intelligent and participatory beginner voters, through an integrated voter education model. This solution was born from the fact that in general voter education only aggressively targets first-time voters during the election stage. This research was carried out by the Pekanbaru City KPU and the Kampar Regency KPU as well as several secondary schools in Pekanbaru City and Kampar Regency. The research used a qualitative design with descriptive methods, with research informants including KPU commissioners, Election Smart House Managers, and Pancasila and Citizenship Education (PPKn) teachers at schools. Research data was collected through observation, interviews, FGD and documentation studies. The research results found that: (1) the absence of a sustainable voter education program to prepare pre-voters to become politically literate beginner voters. Voter education in schools is generally carried out during the election stage, with the theme of socialization; (2) there is no cooperation for the implementation of sustainable voter education (3) an integrated voter education model is needed to combine collaboration between the actors of political education and the PPKn’s teachers as a means of learning about elections and democracy in schools to strengthen students’ political literacy as pre-voters.